FEEDING DETERRANCE OF SOLANUM ELEAGN1FOUU (SOLANALES, SOLANACEAE) AGAINST STORED GRAIN PESTS (Acta Entomológica Chilena, 2023)
Tribolium castaneum and Sitophilus oryzae are the major pests found in Ingeniero White Port, Bahía Blanca, Argentina, one of the most important overseas ports of the country. The widespread use of synthetic insecticides has led to many negative consequences like insecticide resistance resulting in increasing attention given to natural Products. Therefore the objective of this work was to evaluated the alterations produced on the nutritional physiology on T. castaneum larvae and adults, and S. oryzae adults, by polar extracts from leaves and from fruits of S. eleagnifolium. To evalúate the antifeeding activity and the alteration in the nutritional physiology, disks of wheat flour with ethanolic Solutions of the extracts were prepared at concentrations of 0.75,1.6 and 2.4 mg/disk. A control group with ethanol treated disks was prepared. For 72 h these disk were offer to the insects. The weight of the disks and weight of insects were registered before and after the treatment. The nutritional indices were calculated: Relative growth rate (RGR) = (A-B)/(B x day), where A = weight of insects alive on the third day/number of insects alive on the third day; B = original weight of insects/ total number of insects; relative consumption rate (RCR) = D/(B x day), where D = biomass ingested (mg)/number of insects alive on the third day; efficiency of conversión of ingested food (ECI) (%) = (RGR/RCR) x 100 and antifeeding Índex (AI) (%) = [(C-T)/ C] x 100 was calculated where C = consumption of control disks (mg) and T = consumption of treated disks (mg). The polar extracts significantly (p< 0.05) reduced RGR, RCR and ECI in T. castaneum larvae and adults and S. oryzae adults. At the major doses, feeding deterrent action (IA%) was found. In consecuense, the ethanol extracts from leaves and fruits of S. eleagnifolium, produce an antifeedant effect on larvae of T. castaneum and adults of T. castaneum and S. oryzae.
Keywords: Tribolium castaneum, Sitophilus or\/zae, nutritional physiology